PENGARUH PROFITABILITAS DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA SEKTOR HEALTHY CARE PERIODE 2019-2023 - Raharja, Soviandi; Rusnendar, Elan; Aprianti, Vika (LAND JOURNAL, 2025)
This study aims to determine the description and influence of Profitability and Capital Structure on Firm Value. The object of this research is healthy care sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The method used in this research is a quantitative method with a descriptive and verification approach. The population in this study consists of 35 companies, and the sampling technique used is purposive sampling, resulting in a sample of 11 companies with a total of 55 financial reports. The results of this study indicate that partially, Profitability has a significant effect on Firm Value with an influence of 38.2% and a t-test value of 5.654, while Capital Structure has no effect on Firm Value with an influence of 1.8% and a t-test value of 0.934. Simultaneously, the results show that Profitability and Capital Structure influence Firm Value with a total contribution of 37% and an F-test value of 16.764.